اثر الترويج الالكتروني في بناء الصورة الذهنية للخدمة السياحية لدى الزبون - نصيرة،منصر; راضية،بوخزنة; كريمة،عبد المالك; محمد ياسين،عبيدي (university of eloued جامعة الوادي, 2024)
لقد استهدفت هذه الدراسة تحديد اثر عناصر الترويج الالكتروني المختلفة في بناء الأبعاد الثلاثة للصورة الذهنية للخدمة السياحية لدى الزبون، ومن أجل التحقق من ذلك تم توجيه استبيان لعينة من 60 مفردة من زبائن وكالة مكي للسياحة، ومن خلال تحليل أجوبة أفراد العينة وإخضاعها لمختلف المقاييس الإحصائية عن طريق برنامج SPSS V22 تم التوصل إلى أن لعناصر الترويج الالكتروني أثر في بناء الأبعاد الثلاثة للصورة الذهنية ، وذلك بدرجات متفاوتة عند مستوى معنوية 0,05%. This study aimed to determine the effect of the various electronic promotion elements in building the three dimensions of the customer’s mental image of the tourist service. In order to verify this, a questionnaire was directed to a sample of 60 individuals from the customers of Mekki Tourism Agency, and by analyzing the answers of the sample members and subjecting them to various statistical measures about Through the SPSS V22 program, it was found that electronic promotion elements have an impact on building the three dimensions of the mental image, to varying degrees at a significance level of 0.05%.
Keywords: الترويج الالكتروني، الخدمة السياحية، الصورة الذهنية للخدمة السياحية، البعد المعرفي للخدمة السياحية، البعد العاطفي للخدمة السياحية، البعد السلوكي للخدمة السياحية.; electronic promotion; tourism service; mental image of tourism service; cognitive dimension of tourism service; emotional dimension of tourism service; behavioral dimension of tourism service.